2020
DOI: 10.1186/s13287-020-01747-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulp stem cells with hepatocyte growth factor overexpression exhibit dual effects in rheumatoid arthritis

Abstract: Background: To investigate the therapeutic effect of human dental pulp stem cells (DPSCs) transfected with adenovirus expressing hepatocyte growth factor (HGF) in a mouse model of collagen-induced arthritis (CIA). Methods: DPSCs were modified with Ad-HGF to produce HGF-overexpressing DPSCs, DPSCs-HGF. In experimental mouse CIA model, DPSCs-HGF and DPSCs-Null (modified with Ad-Null) were engrafted via intravenously after disease onset, which was determined by the presence of joint swelling. The therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Further radiographic data showed that bone regeneration in the presence of DPSC-HA/TCP was greater than that without DPSCs, which suggests that DPSCs may be a suitable factor for skeletal tissue engineering [43]. Our previous study demonstrated that transplantation of hDPSCs markedly prevented bone loss in the early phase of ovariectomy-induced osteoporosis [31]. Moreover, HGF overexpression in hDPSCs signi cantly enhanced the protective effects against bone loss in vivo.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Further radiographic data showed that bone regeneration in the presence of DPSC-HA/TCP was greater than that without DPSCs, which suggests that DPSCs may be a suitable factor for skeletal tissue engineering [43]. Our previous study demonstrated that transplantation of hDPSCs markedly prevented bone loss in the early phase of ovariectomy-induced osteoporosis [31]. Moreover, HGF overexpression in hDPSCs signi cantly enhanced the protective effects against bone loss in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…hDPSC preparation Clinical-grade hDPSCs were obtained from Beijing SH Biotechnology (http://www.bjshbio.com/). The hDPSCs were prepared as previously described with written consent [31]. In brief, hDPSCs were isolated and cultured in a GMP-compliant facility following ISO 8 clean room standards.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, FoxP3-expressing MSCs prevent rejection of allogeneic grafted liver, increasing the median survival time of treated mice by increasing the numbers of Treg cells and the PD-L1 expression on MSCs ( Qi et al, 2015 ). In other studies, HGF-expressing MSCs exhibited enhanced regenerative and anti-apoptotic effects in murine models of radiation-induced toxicity ( Zhang J. et al, 2014 ; Wang et al, 2015 ), and induction of early immunosuppression in mice undergoing rheumatoid arthritis ( Dong et al, 2020 ). Bcl-2 is also a robust anti-apoptotic protein, which has been overexpressed in MSCs.…”
Section: Engineering Mesenchymal Stromal Cells For Enhancing Their Thmentioning
confidence: 86%
“…However, in the current study, the suppressive effects of hDPSCs on osteoarthritic macrophages generation in the Transwell chamber system remained, which suggested that hDPSCs suppress osteoarthritic macrophages mainly by secreting soluble factors. Numerous reports have demonstrated that hDPSCs highly express HGF, and we previously found that HGF has a pivotal role in controlling the regenerative properties of hDPSCs [ 27 ]. hDPSCs exerted multifaceted benefits for treating experimental rheumatoid arthritis by secreting factors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%